Dispersion and nucleation among nineteenth century Mackenzie Basin Athapaskans: archaeological, ethnohistorical, and ethnographic interpretations - Janes, Robert R. (University of Calgary, 1976)
Bibliography: p. 213-224. The nature of EuroCanadian-Athapaskan interaction is examined in terms of settlement/subsistence behavior for the period 1778- 1900 in the Mackenzie Basin, N.W.T. The fur trade system is isolated intentionally as the primary impetus for nineteenth century Athapaskan adaptive adjustments. The stage for the problem under examination is set through a summary of the environmental and cultural contexts, including both a reconstruction of the aboriginal baseline and a developmental sequence of fur trading facilities in the Mackenzie Basin. The archaeology of nineteenth century EuroCanadian trade is then discussed in an effort to determine the factors affecting the location, distribution and maintenance of the trading establishments. This inquiry into EuroCanadian adaptation is further integrated with an examination of Athapaskan adjustments to ecological, cultural, and historical factors in the nineteenth century. This analysis focuses on 4 aspects of Athapaskan spacing behavior: dispersion, nucleation, mobility, and immobility. The result is a general interpretation of Athapaskan accommodation to the EuroCanadian trade and settlement system , specific to no particular tribal grouping. The essence of this reconstruction is the continuity exhibited between the pre-contact and nineteenth century subsistence/settlement pattern. Additional topics impinging upon this study are discussed in their appropriate context, including differential trade goods acceptance, food and fur overexploitation, pre-adaptation to the fur trade and so forth. There is an attempt to summarize some of these and other related issues in the final chapter.